2020
DOI: 10.1080/14767058.2020.1763952
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pneumonia and pregnancy; a systematic review and meta-analysis

Abstract: Background: The new SARS-CoV-2 originated from Wuhan, China is spreading rapidly worldwide. A number of SARS-CoV-2 positive pregnant women have been reported. However, more information is still needed on the pregnancy outcome and the neonates regarding COVID-19 pneumonia. Material and Methods: A systematic search was done and nine articles on COVID-19 pneumonia and SARS-CoV-2 positive pregnant women were extracted. Some maternal-fetal characteristics were extracted to be included in the meta-analysis. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 29 publications
4
100
1
13
Order By: Relevance
“…disease with the majority of cases occurring in the late second and third trimesters. 10,31,[44][45][46]49,60,[84][85][86][87][88][89][90] Little data are available on the effects of infection occurring in the first or early second trimesters.…”
Section: Maternal Mortalitymentioning
confidence: 99%
“…disease with the majority of cases occurring in the late second and third trimesters. 10,31,[44][45][46]49,60,[84][85][86][87][88][89][90] Little data are available on the effects of infection occurring in the first or early second trimesters.…”
Section: Maternal Mortalitymentioning
confidence: 99%
“…COVID-19 shares several features with SARS-CoV-1 and MERS-CoV, and seems to have a similar pathogenic potential [ 11 , 12 ]. Two early meta-analyses showed that a high percentage of pregnant women affected by these infections experienced unfavourable pregnancy outcomes and that there was no evidence of vertical transmission [ 13 , 14 ]. However, both meta-analyses included small numbers of patients.…”
Section: Introductionmentioning
confidence: 99%
“…(sırasıyla p = 1, p = 0,86 ve p = 0,89) Birinci ve beşinci dakikada Apgar skorlarının ortalaması ise sırasıyla 8,86 ve 9,0 olarak bulunmuştur. (her ikisi için de p <,001) Bu çalışmada dikey bulaşma kanıtı, fetüs veya yenidoğan için herhangi bir tehlike olmadığı gözlemlenmiştir (41) Yapılan bir meta analiz çalışmasında (33 çalışma ve 19 vaka raporunun dahil edildiği) çocukların %17,4'nün (% 95 GA= 9,1-27,3) asemptomatik olduğu, ateş (% 51,2,% 95 GA = 40,2-62,2) ve öksürüğün (% 37,0,% 95 CI = 25,9-48,8) ise en sık semptomlar olduğunu belirlemiştir. Şiddetli veya kritik hastalık prevalansı yaklaşık olarak % 0 olduğu saptanmıştır (% 95 GA = 0-1,0).…”
Section: Virolojiunclassified